Contextual-Based Mathematics Learning Videos on Fifth-Grade Fraction Material - Desak Ketut Sri Galuh; Gusti Ngurah Sastra Agustika (Universitas Pendidikan Ganesha, 2023)
Mathematical concepts that are difficult for students to understand make them easy to forget. This study aims to create a learning media through contextual-based videos in mathematics. It is equipped with an impact evaluation on learning outcomes obtained by students in grade 5 of elementary school. This type of research is developed using the ADDIE model. Four experts and all grade 5 students were used as research subjects. With data collection techniques consisting of interviews, questionnaires, and tests. Data collection instrument with a questionnaire. Data analysis techniques used inferential statistics, descriptive statistical analysis, quantitative descriptive analysis, and qualitative descriptive analysis. The results of the research are that all aspects have been determined valid in the design expert test by 90%, material expert test by 92.30%, learning design expert test by 90.90%, learning media expert test by 91.07%, personal trial by 93.94 %, small group trials 93.69%, and field trials 92.42%. The effectiveness test results show how well the learning video media can be applied to mathematics content. It was concluded that using contextual-based learning video media in the learning process is valid and effective in improving student learning outcomes.